Per una fenomenologia ermeneutica della Complessità di Gadda - Sichera, Antonio (L'ospite ingrato, 2025)
Inspired by the last book on Gadda by Clelia Martignoni, the essay tries to sketch a hermeneutic phenomenology of Gadda’s work, abandoning the psychoanalytic perspective in favour of a different one that aims to a closer fidelity to the texts. The result is a reconstruction of the primal experience from which Gadda’s writing originates, influenced by the Gestalt Therapy model and the fundamental categories of Heidegger’s hermeneutics. La cognizione del dolore sits, naturally, at the core of such analysis.